Water-lubricated pin-on-disc tests with natural fibre reinforced matrix / Ramdziah Md. Nasir - Md. Nasir, Ramdziah (Faculty of Mechanical Engineering & UiTM Press, 2014)
In this study, natural fibre such as paddy straws and cockle shell was chosen due to its abundance and renewable natural fibre reinforced matrix. The fibres were reinforced with polymer using conventional compression molding. The specimen lubricated with water, were slided at different sliding speed using the rotating pin-on-disc friction and wear tests. The best performance under lubricated boundary condition was found for bio-shell cockle reinforced matrix followed by paddy-straw reinforced matrix while pure polypropylene has the highest wear rate and coefficient of friction. With the addition of cockle shell powders or paddy straw, wear rate and coefficient of friction of the material decreases with a minute degree of changes in their properties. The wear mechanism was identified using SEM.